2010
DOI: 10.2298/vsp1010807b
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal delivery versus cesarean section for term breech delivery

Abstract: For breech presentation elective cesarean section remains the major delivery method in nuliparous older than 35 years, while vaginal delivery is considered to be the method of choice in younger multiparous with ultrasonographically estimated neonatal birth weight 2500-3500 grams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 5 publications
2
13
0
5
Order By: Relevance
“…The overall incidence of CS being 72.4% as found out from the present study for singleton term breech was found to be comparable to the study finding made by Zaman SB et al [1] Also, the mean agegroup of 27.17±5.1(SD) is comparable with previous study finding made by Babovic I et al [7] From the present study it was found that CS was done among a high proportion of nulliparous women (73.7%). Study done by Doyle et al showed no significant difference in parity and breech whereas Adel Abu-Heija et al has shown contradicting results.…”
Section: Discussionsupporting
confidence: 90%
“…The overall incidence of CS being 72.4% as found out from the present study for singleton term breech was found to be comparable to the study finding made by Zaman SB et al [1] Also, the mean agegroup of 27.17±5.1(SD) is comparable with previous study finding made by Babovic I et al [7] From the present study it was found that CS was done among a high proportion of nulliparous women (73.7%). Study done by Doyle et al showed no significant difference in parity and breech whereas Adel Abu-Heija et al has shown contradicting results.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, several authors have reported good neonatal outcomes win patients undergoing vaginal breech birth. 12,13,32,33,34 Our study reports good fetal outcome in 87% of babies. 20 babies had low Apgar and required NICU admission but only 2 deaths occurred due to birth asphyxia, the rest were discharged within 1 week.…”
Section: Discussionmentioning
confidence: 58%
“…Several authors have presented evidence that if strict selection criteria are followed before and during labour, vaginal breech delivery is a safe option without associated increase in perinatal morbidity. 12,13 The route of delivery in singleton term breech continues to be debated. Vaginal breech delivery is still being done successfully in places where expertise is available especially in developing countries where women resist caesarean section and often present late in labour to avoid it.…”
Section: Introductionmentioning
confidence: 99%
“…Entre los factores que se han asociado a la presentación de lesiones durante el nacimiento se encuentran la macrosomia fetal, principalmente en fetos con peso superior a 4.500 gramos (4,5), trabajo de parto prolongado, presentación pélvica, desproporción cefalopélvica y aplicación de fórceps (6)(7)(8)(9)(10). También se asocian a procedimientos dianósticos y terapéuticos, y el empleo intempestivo de substancias generadoras de taquisistolia e hipertonía uterina (3).…”
Section: Introductionunclassified
“…Los traumas más frecuentes son la fractura de clavícula, las parestesias braquiales y facial (10)(11)(12), el cefalohematoma y los traumas/heridas en la cabeza, rostro y brazo del RN (13,14). El objetivo del presente estudio fue identificar la incidencia de trauma al nacimiento y sus factores de riesgo asociados.…”
Section: Introductionunclassified